Interindividual differences in trainability and moderators of cardiorespiratory fitness, waist circumference, and body mass responses: a large-scale individual participant data meta-analysis - Bonafiglia, J. T.; Swinton, P. A.; Ross, R.; Johannsen, N. M.; Martin, C. K.; Church, T. S.; Slentz, C. A.; Ross, L. M.; Kraus, W. E.; Walsh, J. J.; Kenny, G. P.; Goldfield, G. S.; et al. (Sports Medicine, 2022)
Although many studies have assumed variability reflects variance caused by exercise training, few studies have examined whether interindividual differences in trainability are present following exercise training. The present individual participant data (IPD) meta-analysis sought to: (1) investigate the presence of interindividual differences in trainability for cardiorespiratory fitness (CRF), waist circumference, and body mass; and (2) examine the influence of exercise training and potential moderators on the probability that an individual will experience clinically important differences. The IPD meta-analysis combined data from 1879 participants from eight previously published randomized controlled trials. We implemented a Bayesian framework to: (1) test the hypothesis of interindividual differences in trainability by comparing variability in change scores between exercise and control using Bayes factors; and (2) compare posterior predictions of control and exercise across a range of moderators (baseline body mass index (BMI) and exercise duration, intensity, amount, mode, and adherence) to estimate the proportions of participants expected to exceed minimum clinically important differences (MCIDs) for all three outcomes. Bayes factors demonstrated a lack of evidence supporting a high degree of variance attributable to interindividual differences in trainability across all three outcomes. These findings indicate that interindividual variability in observed changes are likely due to measurement error and external behavioural factors, not interindividual differences in trainability. Additionally, we found that a larger proportion of exercise participants were expected to exceed MCIDs compared with controls for all three outcomes. Moderator analyses identified that larger proportions were associated with a range of factors consistent with standard exercise theory and were driven by mean changes. Practitioners should prescribe exercise interventions known to elicit large mean changes to increase the probability that individuals will experience beneficial changes in CRF, waist circumference and body mass.